MENGELOLAH KONFLIK YANG TERJADI DIANTARA UMAT TUHAN - Gerry Takaria (Fakultas Filsafat Universitas Advent Indonesia, 2014)
Conflict into the lives of the people of GOD, entered in the various sides.Conflicts occur between members of the members, members of the Council of thechurch, members of the congregation Pastor, between members of Council with themembers of Council, the Council members with Pastor Church. The conflict led to asplit in the body of the people of GOD, if not anticipated or well managed.Pastor, Council and Members of the church need to understand the truefoundation in managing conflict, so as to prevent it or bring disunity that may haveoccurred to the settlement as the Lord wanted. The Bible teaches Christians tomanage conflicts with: 1. vision is thanks to GOD, who invites the parties to theconflict to continue to love each other properties; 2. The charge was Justice GOD,all efforts should be emphasized to the completion of GOD justice is not justiceaccording to human, thus bringing the conflicting parties to a win-win result; 3.Make it happen in accordance with the Truth GOD, foundation to every problemmust be based on the truth of GOD, not truths sinful man; 4. The process ofreconciliation, to bring all issues to the restoration of relationships that resolve alldifferences.